Maternal and fetal outcome among pregnant women following open heart surgery - Ranjan, Redoy; Akhter, Nargis; Adhikary, Asit Baran; Uddin, Md. Aftab (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this retrospective cohort study was to evaluate the pregnancy outcome following open heart surgery for three years. Group I (n = 37) included pregnancy with history of intracardiac repair except valvular heart disease, while Group II (n = 19) included pregnancy with prosthetic valve received anticoagulation therapy. In total, 78.6% pregnancies ended in healthy live births, and 19.6% pregnancies terminated in abortion (8.1% patients in Group I and 42.1% patients in Group II). 5.3% baby was born with congenital malformation in Group II. Mean birth weight was found 2.8 ± 0.6 kg in Group I and 2.5 ± 0.3 kg in Group II. The mean APGAR score was found 8.5 ± 0.7 in Group I and 8.1 ± 0.7 in Group II. 19.6% patients developed cardiac complications during the pregnancy. Majority of the patients (89.2% in Group I and 63.2% in Group II) was found good health status. Proper antenatal care and early risk stratification are the fundamental measures to improve the maternal and fetal outcome in a patient of open heart surgery.